Metals, Nanoparticles, Particulate Matter, and Cognitive Decline - Calderón-Garcidueñas, Lilian; Chávez-Franco, Diana A.; Luévano-Castro, Samuel C.; Macías-Escobedo, Edgar; Hernández-Castillo, Ariatna; Carlos-Hernández, Esperanza; Franco-Ortíz, Agustina; Castro-Romero, Sandra P.; Cortés-Flores, Mónica; Crespo-Cortés, Celia Nohemí; Torres-Jardón, Ricardo; Stommel, Elijah W.; et al. (Frontiers in Neurology, 2022)
Combustion metal rich, highly reactive nanoparticles (NP) reach the brain in highly exposed fine particulate matter (PM2.5) urban residents. Exposure to metals is ubiquitous and emission sources include: gasoline, diesel, smoke from wildfires, contaminated soil, water and food, medical implants, waste recycling facilities, subway exposures, and occupational environments. PM2.5 exposure is associated with impaired cognitive performance, neurobehavioral alterations, incidence of dementia and Alzheimer’s disease (AD) risk. Heavy duty diesel vehicles are major emitters of metal rich PM2.5 and nanoparticles in Metropolitan Mexico City (MMC). Cognitive impairment was investigated in 336 clinically healthy, middle class, Mexican volunteers, age 29.2±13.3 years with 13.7±2.4y education using the Montreal Cognitive Assessment (MoCA). MoCA scores varied with age and residency in three Mexican cities with cognition deficits impacting ~74% of the young middle-class population (MoCA≤25). MMC residents ≥31y (x̄46.2±11.8y) had MoCA x̄20.4±3.4 versus low pollution controls 25.2±2.4 (p<0.0001). Formal education years positively impacted MoCA total scores across all participants (p<0.0001). Residency in PM2.5 polluted cities impacts multi-domain cognitive performance. Identifying and making every effort to lowering key pollutants impacting neural risk trajectories and monitoring cognitive longitudinal performance are urgent.PM2.5 emission control should be prioritized, metal emissions targeted and neuroprevention interventions implemented early.